Effects of Cyber Disruption in a Distributed Team Decision Making Task. (September 2013) - Finomore, Victor; Sitz, Adam; Blair, Elizabeth; Rahill, Katherine; Champion, Michael; Funke, Gregory; Mancuso, Vincent; Knott, Benjamin
Stories of cyber-attacks have been prevalent in the public media and the cyber security market has grown greatly to help meet this demand. However, much of the effort has been focused on development of better hardware and software solutions with little thought to the human factors of cyber security. This investigation sought to gain a better understanding of the influence cyber-attacks have on the decision-making and collaboration of distributed team members working together to solve a complex logic problem. Eight three-person teams worked together to piece together bits of information to solve a potential terrorist attack. The time and outcome scores were evaluated for the three experimental conditions, which varied the levels of information injected. The goal of the injected statements was to disrupt the decision-making and collaborative process. Injects that were explicitly negating true facts had the more detrimental effect on team performance while performance in the condition with injects that were more suggestive in nature were no different from the no inject condition. These results shed light into the breakdown in team decision-making when confronted with a contradictory fact thus aiding in our knowledge to build robust collaborative tools.